Multimodality endoscopic treatment for tracheobronchial stenosis secondary to endobronchial tuberculosis - Nai, Chien Huan; Khai, Lip Ng; Mohammad, Fatimah Azmah; Mohd Aminudin, Nur Husna; Muhammad, Noorul Afidza; Daut, Ummi Nadira; Nasaruddin, Mona Zaria; Abdul Rahaman, Jamalul Azizi (European Respiratory Society, 2021)
Introduction: Tracheobronchial stenosis secondary to endobronchial tuberculosis (TSTB) is a rare but devastating complication of TB. Endoscopic interventions (EI) might be an attractive alternative for patients unfit for surgery but little is known on whether the efficacy of EI can be affected by airway features.